Endogenous Endophthalmitis: A Case Report of Lemierre's Syndrome Originating from Pharyngotonsillitis - Gorrotxategi, Nerea Gangoitia; Garmendia, Iñigo Salmeron; Heras-Mulero, Henar; Arbués, Santiago López; Silva, Esther Compains (Medical Science: Trends and Innovations Vol. 6, 2025)
Background: Lemierre’s Syndrome is characterized by infectious thrombophlebitis, typically affecting the internal jugular vein (IJV), resulting in multiorgan involvement, with Fusobacterium Necrophorum considered as the most associated organism. Ophthalmic complications of Lemierre’s Syndrome have rarely been reported in the literature. Objective: The objective of the study is to report a case of Lemierre’s Syndrome producing unilateral endogenous endophthalmitis in a healthy, young woman with a history of tonsillitis. Case Report: A 17-year-old healthy woman developed a fever after a few days of sore throat. The patient later developed pneumonia with septic signs, leading to admission to the Intensive Care Unit. Lemierre Syndrome was diagnosed due to multiple septic pulmonary emboli and signs of sepsis following a recent episode of tonsillitis. During hospitalization, the patient complained of decreased visual acuity and floaters in her left eye. Ophthalmological examination revealed papillary edema, vitritis, foci of chorioretinitis in the macula and Roth’s spots, confirming the diagnosis of endogenous endophthalmitis. Subsequently, the patient underwent appropriate treatment, progressing satisfactorily. Conclusion and Importance: Although ophthalmological manifestations are rare, due to the pathophysiological characteristics of Lemierre’s Syndrome, all patients should undergo standard ophthalmologic assessment, even in the absence of ophthalmic symptoms or visible findings, as part of a multidisciplinary management approach. Early administration of both systemic and intraocular antibiotics should be the mainstay of treatment for most patients, as endophthalmitis can often lead to devastating ocular and systemic consequences.